TI_GERICHTE 12.2004.13 vom 8. Oktober 2004 , licenziamento in tronco per aver svolto le ferie senza autorizzazione - TI Tribunale d'appello (2004)
licenziamento in tronco per aver svolto le ferie senza autorizzazione